INCIDENCE OF BRADYCARDIA IN INFANTS UNDERGOING INTUBATION WITH OR WITHOUT ATROPINE - MUSHTAQ, S; FAISAL, S; BUTT, AB; AARAJ, S; ZAFAR, GM; ARSHAD, M; ADIL, H (Biological and Clinical Sciences Research Journal, 2024)
Bradycardia is a life-threatening arrhythmia that endangers life by compromising blood flow to the brain. During intubation, its prevention is life-saving—the benefit of atropine in preventing bradycardia before intubation is controversial in the literature. Objective: The objective of the study was to find and compare the incidence of bradycardia with and without atropine. Methods: This single-centre randomised controlled trial was conducted at a tertiary care pediatric emergency department for six months. After applying inclusion and exclusion criteria, children were divided into two groups. Group 1 was given atropine before intubation, and group 2 was not. The overall incidence of bradycardia in subgroups was noted, along with the number of attempts and intubation time. Data was analysed using SPSS 26.0. Results: 86 patents were included in the study, with 43 in both groups. The mean age of the participants was 69.02+109.10 days. 48 (55.8%) were males and 38 (44.2%) were females. The incidence of bradycardia was 7% (6 Patients), with no statistically significant difference in both the groups (p-value was greater than 0.05). The number of attempts for intubation and intubation duration was also neither associated with bradycardia nor with atropine use. (p-value> 0.05).Conclusion: There is a higher incidence of bradycardia during intubation in children, with no significant difference in its occurrence with the use of atropine.